Progression independent of relapse activity and relapse-associated worsening in seronegative NMOSD: an international cohort study - Siriratnam, Pakeeran; Huda, Saif; Van der Walt, Anneke; Sanfilippo, Paul; Sharmin, Sifat; Foong, Yi Chao; Yeh, Wei Zhen; Zhu, Chao; Khoury, Samia J; Csepany, Tunde; Willekens, Barbara; Etemadifar, Masoud; et al. (Journal of neurology, 2025)
BACKGROUND: Previous studies have indicated that progression independent of relapse activity (PIRA) is uncommon in patients with aquaporin- 4 antibody-positive (AQP4-IgG) neuromyelitis optica spectrum disorder (NMOSD). However, the patterns of disability accumulation in seronegative NMOSD are unknown. This study aimed to evaluate the prevalence of PIRA and relapse-associated worsening (RAW) in seronegative NMOSD. METHODS: We conducted a retrospective, multicentre cohort study of seronegative NMOSD patients from the MSBase registry. Inclusion criteria required at least three recorded expanded disability status scale (EDSS) scores: baseline, progression, and 6 months confirmed disability progression (CDP). For those with 6-month CDP, the presence or absence of relapse between baseline and progression determined the classification as RAW or PIRA, respectively. Descriptive statistics were employed to present the data. RESULTS: This study included 93 patients, with a median follow-up duration of 5.0 years (Q1 2.8, Q3 8.4). The cohort predominantly consisted of female patients (77.4%), with a median age of onset of 33.9 years (Q1 26.1, Q3 41.2). PIRA was observed in 1 case (1.1%), whilst RAW was documented in 7 cases (7.5%). CONCLUSION: This international cohort study confirms that CDP is uncommon in seronegative NMOSD. Given more than three quarters of CDP occur due to RAW, therapeutic strategies should focus primarily on preventing relapses.
Keywords: Registries; Recurrence; Adult; Neuromyelitis Optica; NMOSD; Disease Progression; Autoantibodies; Humans; progrese nemoci; recidiva; akvaporin 4; ženské pohlaví; Cohort Studies; Relapse-associated worsening; Follow-Up Studies; Aquaporin 4; mladý dospělý; dospělí; Seronegative; Female; Progression independent of relapses; retrospektivní studie; mužské pohlaví; neuromyelitis optica; Male; Disability; EDSS; Young Adult; lidé středního věku; posuzování pracovní neschopnosti; následné studie; registrace; Retrospective Studies; Middle Aged; kohortové studie; lidé; autoprotilátky; Disability Evaluation